Neurology Telemusic Program at the Time of the COVID-19 Pandemic: Turning Hospital Time Into Aesthetic Time During Crisis - Bonakdarpour, Borna; McFadden, Alyssa; Zlotkowski, Skye; Huang, Daniel; Shaker, Michelle; Shibata, Bailey; Haben, William; Brashear, Charlinda; Sandoval, Anny; Breitenbach, Carianne; Rodriguez, Caren; Viamille, Jennifer; et al. (Frontiers in Neurology, 2021)
Strict precautions during the COVID-19 pandemic left patients isolated during already stressful hospital stays. Research indicates that listening to music recruits regions in the brain involved with social interaction and reduces feelings of loneliness. We formed a team of clinicians and clinical musicians to bring music to the bedside, as “psychological first aid.” Our goal was to reduce feelings of anxiety and isolation in patients admitted to the Northwestern Memorial Hospital's neurosciences unit. Participants were offered 30–40-min live music sessions over FaceTime by a violist in consultation with a music therapist and a certified music practitioner. Music used for the interventions was personalized. Participants were evaluated with the Music Assessment Tool where they indicated their musical preferences and music to which they objected. Following the intervention, participants answered a questionnaire assessing how music impacted their emotional state based on a 1–10 Likert scale. Scores were then averaged across all patients and were calculated as percentages. Eighty-seven sessions were completed during a 3-month period. Despite different degrees of disability, most patients engaged aesthetically with the music. The likelihood to recommend (LTR) for the program was 98%; participants tended to highly agree that the intervention improved their emotional state (92%); that it provided a pleasurable experience (92.4%); and that it reduced their stress and anxiety (89.5%). This pilot project showed that the telemusic intervention was feasible for our neurosciences patients during the COVID-19 pandemic. Our results are consistent with previous in-person hospital-based music interventions and highlight the importance of such programs when in-person interventions are not possible. This pilot project serves as a prelude to further investigate mechanisms by which music interventions can support admitted neurology patients.